Critical discussion of a shading calculation method for low energy building and passive house design. (October 2017) - Winkler, Matthias; Antretter, Florian; Radon, Jan
Abstract: Solar energy gains are among the most important aspects in the design of very low energy buildings like passive houses. An optimization of solar gains reduces the required heating demand, however too high solar gains can lead to overheating issues. Most methods for building energy ratings and building energy certificates use a monthly balance based calculation procedure. Also the current methodology for passive house assessment and certification is a monthly balance based one. To incorporate shading by fixed elements as an influence on solar gains into those methods, some simplifications are necessary. This paper discusses the current implementation of the shading calculation in the passive house verification method. Based on comparison tests of the current method with an advanced shading calculation method shortcomings of the existing method are discussed. It is shown that the current algorithms for static calculation sometimes give erroneous and unreliable results. The impact on the different assessment criteria, energy demand and loads as well as overheating, exceeds acceptable margins of error.